The developmental state in the 21st century: calling for a new social contract - Georgeta Vidican Auktor; Giulio Regeni (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
Giulio Regeni: In memoriam Almost a year ago, on 13 January 2016, I had my last Skype conversation with Giulio, when he called from Cairo where he was conducting his field research for his doctoral studies. We exchanged thoughts on finalising the draft of this paper, which was the result of our collaboration during his time as a visiting researcher at the German Development Institute in the summer of 2015. A few days later, on 25 January, alerts on his sudden disappearance reached us. He was found lifeless on 3 February on the outskirts of Cairo, with signs of extreme torture. Giulio's brutal passing, most probably at the hands of an increasingly repressive and paranoid Egyptian state, shocked not only those of us who knew him closely but also the larger development and regional studies community and social activist groups. This loss made it impossible for me to finish this draft for several months afterwards. Giulio, with a brilliant mind, a passion for development, and great faith in humanity, was an inspiration for those he engaged with. His understanding of the development process was shaped by scholars such as Alice Amsden, Diane Davis, Ha-Joon Chang and Peter Evans, clearly evidenced in this Discussion Paper. His precise writing skills and commitment to understanding sources of development are reflected throughout this joint effort, especially in Sections 2 and 4. Finalising this important paper without Giulio was hard as I was certain that these ideas would have benefited significantly from his insights. I do hope, however, that he would have enjoyed reading this final draft.Giulio, you will never be forgotten! Georgeta Vidican Auktor Abstract The `developmental state' is a highly debated notion in development literature, having evolved from the extraordinary experience of late industrialising countries in East Asia. In this Discussion Paper we join a growing number of scholars to argue that changing global conditions call for a revitalisation of the debate on the role of the state in social and economic transformation in the 21st century. We focus on three main global challenges for economic development in the 21st century: climate change and environmental degradation; increased digitalisation (the increasingly `bit-driven' economy); and changed policy space for individual states as a result of globalisation. These evolve simultaneously and reinforce each other. We argue that the global context calls for a change in the social contract that underpins structural economic transformation, by placing a stronger emphasis on cultivating inclusive state-society relations oriented towards promoting economic growth within planetary boundaries. Such emphasis is, in our view, currently under-represented in the emerging literature on a developmental state in the 21st century. For this reason, we consider it relevant not only to elaborate on the historical conditions that shaped the role of the state in industrial policy in late industrialising countries, but also on current challenges that call for a changing perspective on the role of the state in emerging and developing countries.
Keywords: 330; Governance; Technologie und Innovation